STUDENTS’ UNDERSTANDING OF GENERIC STRUCTURE OF THE TEXT AND THE QUALITY OF WRITING: A CORRELATIONAL STUDY - Wati, Atikah (Jurnal Bahasa Inggris, 2018)
Indriyani et al, (2013) stated that many students had dificulty in understanding the generic structure of analytical exposition text. Therefore, the present study tried to investigate the correlation between students understanding in writing generic structure of analytical exposition and the quality of students? writing in second grade of senior hight school. Grounded in explanatory correlational research design by Creswell (2011), this study conducted over two weeks in one of senior high school in Indramayu. Close-ended questionnaire and writing test were instruments to collect the data and it was analyzed  by using SPSS 22. The statistical calculation from students understanding in writing generic stucture of the text and writing test indicated that the value of tcount was 3.23 and the value of ttable was 0.361. It can be concluded that the hypothesis was accepted because tcount 3.23 > ttable 0.361. The finding reveal that there was middle correlation or middle prediction in students understanding of generic structure of analytical exposition and students writing quality with the score 0,52.